Peace and Conflict Impact Assessment of Development Intervention on Conflict Dynamics in Gbaramatu Kingdom - Jarikre, Mathias (NIU Journal of Social Sciences, 2024)
Infrastructural deficit accentuates the narratives on conflict and development trap in communities of Nigeria’s Niger Delta Region. Development intervention is a widespread strategy to address intractable conflicts in the region. This article examines peace and conflict impact assessment of development initiatives by Delta State Oil Producing Areas Development Commission on conflict dynamics in Gbaramatu Kingdom. The article adopted both survey and case study designs, using development projects in Okerenkoko and Oporoza communities. Empirically, indicators were carefully formulated to measure impact of development intervention and shed light on conflict dynamics against the backdrop of delta-wide analysis. The underpinning assumption was that development projects have heightened tension in Gbaramatu communities, the seat of militant resistance to the Nigerian government. This assumption was tested by an analysis of conflict indicators and lived experiences. Empirical evidence seems to affirm that this does not hold true in Gbaramatu communities that are yearning for rapid infrastructure development. Keywords: Peace and conflict impact assessment, conflict dynamics, project partner, development intervention, Gbaramatu Kingdom, Delta State Oil Producing Area Development Commission.